Sistem Informasi Penjualan Dan Pemesanan Mukena Berbasis Online - Ilham Maulia; Firdaus (Universitas Putra Indonesia YPTK Padang, 2021)
The rapid development of information technology has significantly impacted the need for fast, accurate, and relevant information in the business world. Proper use of technology can help companies improve information quality through computerized systems, allowing data to be neatly organized, structured, and securely stored in databases. One technology widely utilized in the business world is the website, which serves not only as an information medium but also as a means of online product sales and promotion. Sales systems that still rely on direct interaction with customers and are centered on specific locations make it difficult for companies to expand their market, increase promotions, and maintain competitiveness amidst a growing number of competitors. Furthermore, limited access to product information, inflexible promotional media, and rising operational costs hinder the sales process. Taltuis Distributor Padang, a mukena distributor in Padang City, is in need of innovation to expand its product promotion and marketing both domestically and internationally. Therefore, a web-based sales and ordering information system was developed to simplify the online product promotion, ordering, and sales process, thereby expanding market reach, improving customer service, and supporting increased company profits